Does the cognitive activity can generate student’s physics argumentation performance features? - Viyanti, Viyanti; Cari, Cari; Prasetyo, Zuhdan Kun; Maulina, Hervin (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2020)
A performance feature is a domain-specific to the organization of knowledge. Well-organized knowledge is characterized when students are able to collaborate the knowledge features of the physics problem. The knowledge feature can be a cognitive activity where teachers influence students by changing the pattern of knowledge from